Valuing the contribution of blue carbon to small island developing states' climate change commitments and Covid-19 recovery. Issue 132 (June 2022) - McHarg, Ellen; Mengo, Elena; Benson, Lisa; Daniel, Jody; Joseph-Witzig, Andre; Posen, Paulette; Luisetti, Tiziana
Abstract: Small Island Developing States (SIDS) face complex socio-economic and environmental threats, making them particularly vulnerable to climate change. Blue Carbon (BC) ecosystems (mangrove forests, tidal marshes, and seagrass meadows) provide climate regulation services by sequestering and storing carbon, presenting an opportunity for SIDS to address climate change and implement Paris Agreement commitments in their Covid-19 recovery. BC habitat decline not only reduces carbon sequestration benefits provided, but can also result in sediment disturbance and the release of previously stored carbon back into the atmosphere. In this work, a scenario analysis informed by a stakeholder workshop and scientific and socio-economic expectations is used to assess the economic importance of Grenada's BC (mangroves and seagrasses) over the next 10, 25 and 50 years. Our findings indicate that sequestration benefits are severely diminished under Business-as-Usual habitat loss, but still marginally outweigh losses from carbon emissions, with overall welfare gains of US0.5–1.9 million over 50 years. To stimulate economic recovery post-pandemic, stakeholders anticipated a realistic scenario of increased habitat decline resulting in overall losses of US5.4–19.4 million in the next 50 years. However, if ecosystems are maintained, overall carbon benefits could reach US10.7 million, while a 20% increase in mangroves over the next 25 years provides benefits reaching US11.1 million between 2020 and 2070. These results demonstrate a significant increase in value when BC ecosystems are maintained and not disturbed, preventing the release of previously stored carbon and enhancing sequestration capacity. Restoration benefits are marginal, compared to conservation, supporting claims that conservation is more cost effective. Highlights: A scenario analysis is used to value Grenada's BC climate mitigation service. Maintaining BC extents retains sequestration worth up to 10.7million over 50 years. BAU habitat loss lowers sequestration and releases stored carbon, reducing benefits. More severe habitat declines result in welfare losses up to US19.4million by 2070. Integrating BC into SIDS' Paris Agreement commitments can enrich climate mitigation.